2015
DOI: 10.1037/xhp0000026
|View full text |Cite
|
Sign up to set email alerts
|

On the independence of visual awareness and metacognition: A signal detection theoretic analysis.

Abstract: Classically, visual awareness and metacognition are thought to be intimately linked, with our knowledge of the correctness of perceptual choices (henceforth metacognition) being dependent on the level of stimulus awareness. Here we used a signal detection theoretic approach involving a Gabor orientation discrimination task in conjunction with trial-by-trial ratings of perceptual awareness and response confidence in order to gauge estimates of type-1 (perceptual) orientation sensitivity and type-2 (metacognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 30 publications
8
75
0
Order By: Relevance
“…Unfortunately, most attempts to induce blindsight-like behavior in normal observers -typically using visual masking or other similar techniques --are susceptible to response bias confounds (Charles, King, & Dehaene, 2014;Charles, Van Opstal, Marti, & Dehaene, 2013;Eriksen, 1960;Hannula, Simons, & Cohen, 2005;Jachs et al, 2015;Lloyd, Abrahamyan, & Harris, 2013;Merikle, Smilek, & Eastwood, 2001;Ramsøy & Overgaard, 2004) . Further, past attempts to remedy response bias concerns (Kolb & Braun, 1995;Kunimoto, Miller, & Pashler, 2001) have met with their own conceptual or replicability challenges (Evans & Azzopardi, 2007;Galvin, Podd, Drga, & Whitmore, 2003;Morgan, Mason, & Solomon, 1997;Robichaud & Stelmach, 2003) .…”
Section: Normal Observers Show No Evidence For Blindsight In Facial Ementioning
confidence: 99%
“…Unfortunately, most attempts to induce blindsight-like behavior in normal observers -typically using visual masking or other similar techniques --are susceptible to response bias confounds (Charles, King, & Dehaene, 2014;Charles, Van Opstal, Marti, & Dehaene, 2013;Eriksen, 1960;Hannula, Simons, & Cohen, 2005;Jachs et al, 2015;Lloyd, Abrahamyan, & Harris, 2013;Merikle, Smilek, & Eastwood, 2001;Ramsøy & Overgaard, 2004) . Further, past attempts to remedy response bias concerns (Kolb & Braun, 1995;Kunimoto, Miller, & Pashler, 2001) have met with their own conceptual or replicability challenges (Evans & Azzopardi, 2007;Galvin, Podd, Drga, & Whitmore, 2003;Morgan, Mason, & Solomon, 1997;Robichaud & Stelmach, 2003) .…”
Section: Normal Observers Show No Evidence For Blindsight In Facial Ementioning
confidence: 99%
“…Hence, the results are in keeping with the proposal that metacognitive confidence and visual awareness can be dissociated (see also 21 ) and with the view that higher-order cognitive processes are to some extent dissociable from conscious experience. 11,22,23 Most important for the aims of the present study, we observed that the current prospective belief of performance success could be predicted based on the pattern of visual awareness, task-confidence, and task-correctness, notably from several trials back. The prediction of this belief was strongest considering information from the most recent previous trial, with classification performance decreasing with longer time windows.…”
Section: Discussionmentioning
confidence: 60%
“…Most critically, previous research indicates that d' and meta-d' can be sensitive to different factors. For instance, using a similar paradigm to the one used in this study, we have previously shown that visibility has a strong effect on d' but not on meta-d', 11 indicating that meta-d' and d' are not necessarily based on a similar process, or operate on a similar type of information (see also 21 ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations